2001
DOI: 10.1086/319992
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Is a Key Pathogen in Hemorrhagic Cystitis Associated with Bone Marrow Transplantation

Abstract: Late-onset hemorrhagic cystitis (HC) is a well-known complication of bone marrow transplantation (BMT) that is mainly attributed to infection with BK virus (BKV) and adenovirus (AdV). From 1986 through 1998, 282 patients underwent BMT, and 45 of them developed HC. Urine samples tested positive for AdV in 26 patients, of which 22 showed virus type 11. Among patients who underwent allogeneic BMT, logistic regression analysis revealed acute graft-versus-host disease (grade, > or = 2) to be the most significant pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
91
4
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 13 publications
9
91
4
3
Order By: Relevance
“…However, like our case, there are reports when patients have acquired adenovirus infection after 100 days post-BMT [7]. Regarding the associated risk factors involved in acquiring adenovirus infections are type of transplant (allogeneic vs autologous), history of aGVHD, use of immunosuppressive drugs, use of conditioning regimen containing cyclophosphamide, fludarabine or TBI, younger age group, asymptomatic viremia, unrelated donor, adenovirus antibody status of donor, T cell depletion of stem cell harvest [6,[8][9][10][11].…”
Section: Discussionmentioning
confidence: 59%
“…However, like our case, there are reports when patients have acquired adenovirus infection after 100 days post-BMT [7]. Regarding the associated risk factors involved in acquiring adenovirus infections are type of transplant (allogeneic vs autologous), history of aGVHD, use of immunosuppressive drugs, use of conditioning regimen containing cyclophosphamide, fludarabine or TBI, younger age group, asymptomatic viremia, unrelated donor, adenovirus antibody status of donor, T cell depletion of stem cell harvest [6,[8][9][10][11].…”
Section: Discussionmentioning
confidence: 59%
“…27 However, it must be remembered that CMV and adenovirus 28 also have been associated with the development of hemorrhagic cystitis, sometimes in association with BK virus. [28][29][30][31][32] Among the papovavirus family, JC virus has been reported as a cause of multifocal leukoencephalopathy in cancer patients receiving chemotherapy and rituximab, in one case combined with autologous HSCT. 33,34 Parvovirus B19 has been reported to cause persistent infection (several months or years) in immunocompromised hosts mainly due to impairment of B-cell function.…”
Section: Allogeneic Hsctmentioning
confidence: 99%
“…As adenovirus serotype 11 (AdV11) with striking tropism for the urinary system is a pathogen predominantly responsible for late-onset HC after allogeneic HSCT in Japan, 1,2 it is important to assess the risk of AdV-HC and to make a rapid diagnosis of HC for early intervention.…”
mentioning
confidence: 99%
“…According to the published criteria, 3 we recorded grade 2 or higher HC as a clinically important complication in HSCT patients and performed viral cultures of their urine. As Akiyama et al 2 reported that the viral culture is equivalent to PCR for diagnosis of AdV-HC, we classified HC into AdV-HC and nonAdV-HC based on the culture results. Among 69 subjects, 15 patients developed late-onset HC during the 1-year follow-up period ( Figure 1a).…”
mentioning
confidence: 99%
See 1 more Smart Citation